Science fiction the best of 2003 - Haber, Karen; Strahan, Jonathan (New York Ibooks distributed by Simon & Schuster, 2004)
Bringing together writers such as Christopher Priest, Brian W. Aldiss, Ian MacLeod and Orson Scott Card, "Science Fiction: the best of 2003", also showcases the best writing from magazines and the Internet.
Introduction / Karen Haber -- Fluted girl / Paolo Bacigalupi -- Study in emerald / Neil Gaiman -- Flowers from Alice / Cory Doctorow and Charles Stross -- Tale of the golden eagle / David D. Levine -- Bernardo's house / James Patrick Kelly -- Confusions on Uni / Ursula K. Le Guin -- Jon / George Saunders -- Cookie monster / Vernor Vinge -- Legions in time / Michael Swanwick -- Chop line / Stephen Baxter -- Calling your name / Howard Waldrop -- Empire of ice cream / Jeffrey Ford -- Bumpship / Susan Mosser -- Only partly here / Lucius Shepard.
Keywords: Science fiction, American; Science fiction, English